Social Media as a Learning Platform for EFL Learning: A Case of Undergraduate Students (The Mega Journal, 2024)
Social media is one of the most popular learning platforms among youths, especially for the university level EFL students. The paper aims to explore how undergraduate level EFL students in a university utilize social media to improve their English writing skills. Using a meta-analysis approach, seventeen peer-researched articles published in the last five years were downloaded from google scholar and closely reviewed. Based on the review, the study concluded that social media was used as one of the informal learning platforms for writing in English. Students were reported to have been engaged in independent writing in social media while communicating with their peers, and relatives, thereby developing confidence in writing in English, though the use of more informal language structures were preferred. The findings of the study imply that higher engagement of EFL students in social media communication positively impacts their writing skills, so institutions are to increase the use of ICT in their pedagogical practices for students’ meaningful learning.